Differential force degradation of intermaxillary latex and non-latex elastics in vitro - Oscar Andrés Montenegro-Moncayo; Jenny Adriana Mosquera-Hurtado; Gretel González-Colmenares; Yeily Isabel Thomas-Alvarado (Universidad de Antioquia, 2018)
Introduction: Various in vitro studies report that latex and non-latex elastics lose some of their initial force after they have been placed in the oral cavity. However, several differences occur within one single manufacturer, which could be of importance in selecting elastics. The aim of the present study was to conduct an in vitro evaluation of force loss in latex and non-latex elastics of a same manufacturer, activated in conditions simulating the oral cavity. Methods: we used 40 intermaxillary latex (n = 20) and non-latex (n = 20) ¼" 6 oz (170.10 g) elastics, stretched to 18 mm and immersed in artificial saliva for 24 hours. Force-displacement was measured using a test dynamometer, calculating the percentage of force relaxation (%R) at 0, 6, 12, 18, and 24 hours. The Kruskal-Wallis test was used to compare the groups. Results: latex elastics significantly offered greater force than non-latex elastics during all evaluations (p < 0.05). The %R in latex elastics at 24 hours was 8.7% and 9.2% in non-latex elastics. The largest force loss in both materials occurred during the first six hours. The difference in %R between the two materials was statistically significant between 0 and 6 hours. Conclusions: the latex and non-latex elastics used in this study can be equally used in clinical practice. However, the use of both elastics must be kept under strict control to achieve efficient orthodontic mechanics, since the period of greatest instability occurred between 0 and 6 hours.